Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s13072-023-00484-9
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel interrogation of H3.3 reveals a primordial role in transcription regulation

Abstract: Background Eukaryotic cells can rapidly adjust their transcriptional profile in response to molecular needs. Such dynamic regulation is, in part, achieved through epigenetic modifications and selective incorporation of histone variants into chromatin. H3.3 is the ancestral H3 variant with key roles in regulating chromatin states and transcription. Although H3.3 has been well studied in metazoans, information regarding the assembly of H3.3 onto chromatin and its possible role in transcription re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…RebL1 in this region might be involved in transcription repression or chromatin remodeling. RebL1-FZZ localizes in the MAC and micronuclear localization disappears with changes in the cell cycle (Nabeel-Shah et al 2023 ). However, we found that the signal of RebL1-HA did not disappear in MIC, rather it performed positional shifts during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…RebL1 in this region might be involved in transcription repression or chromatin remodeling. RebL1-FZZ localizes in the MAC and micronuclear localization disappears with changes in the cell cycle (Nabeel-Shah et al 2023 ). However, we found that the signal of RebL1-HA did not disappear in MIC, rather it performed positional shifts during the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although Caf1b and Hir1 interacting proteins were detected previously, specific interactors for Hir1 and Caf1b under different development stages were less clear [49]. To further investigate the function of Caf1b and Hir1, interactors of Caf1b and Hir1 were identified.…”
Section: Caf1b and Hir1 Interacted With Different Interactorsmentioning
confidence: 94%